Pengaruh Beberapa Formula Pupuk Terhadap Sifat Kimia Tanah dan Hasil Tanaman Sawi Hijau (Brassica juncea L.) di Subak Tegal Lantang Kecamatan Denpasar Barat - SAPUTRA, MADE KRISNANDA ADI; SUSILA, KETUT DHARMA; KUSMIYARTI, TATI BUDI (Agrotrop : Journal on Agriculture Science; Vol 10 No 2 (2020)DO - 10.24843/AJoAS.2020.v10.i02.p02, 2020)
Effect of Some Fertilizer Formulas on Soil Chemical Properties and Yield of Green Mustard ( Brassica juncea L.) in Subak Tegal Lantang, West Denpasar District . The aims of this study is to determine the effect of several fertilizer formulas on soil chemical properties and yield of green mustard ( Brassica juncea L.) in Subak Tegal Lantang, West Denpasar District. This study used a Randomized Block Design (RBD) consisting of 6 treatments including controls and repeated 4 times with a total of 24 treatment plots. Fertilization treatment consists of three types of fertilizers, namely organic fertilizer, inorganic fertilizer, and biofertilizer. The fertilizer formula tested consisted of P0 = control (without fertilizer), P1= 5 tons of compost ha -1 + 300kg Phonska ha-1 + 200kg Urea ha -1 , P2= 5 tons of compost ha -1 + 300kg Phonska ha -1 + 200kg Urea ha -1 + biofertilizer (1 cc / liter water / plot), P3= 10 tons of compost ha -1 + 300kg Phonska ha-1 + 200kg Urea ha -1 , P4= 10 tons of compost ha -1 + 300kg Phonska ha -1 + 200kg Urea ha -1 + biofertilizer (1 cc / liter of water / plot), P5= biofertilizer with a concentration of 1 cc / liter of water / plot. The data from the observed parameters then analyzed statistically using analysis of variance (Anova) to determine the significance of the treatment. If it has a significant effect on the parameters observed, then it will be followed by the LSD test at the 5% real level. The results of study showed that the fertilizer formula treatment had a very significant effect on organic-C (P <0,01) and significantly affected the plant fresh weight (P <0,05), but had no significant effect on the acidity (pH), total-N, available-K, available-P, cation exchange capacity, base saturation, plant height, number of leaves, and plant dry weight. The P4 fertilizer formula gave the highest increase in soil organic-C content significantly by 2.99% or an increase of 66% compared to the control and gave the highest yield of fresh greens mustard by 23.64 tons ha -1 .